PENERAPAN CITIZEN JOURNALISM PADA KONTEN DIGITAL VLOG YOUTUBE MENGENAI MUSEUM SRI BADUGA - Raessa Adliashany; Hadi Purnama (Media Nusantara, 2018)
Vlog or video blog is a new trend in society since the birth of social media erawhich is accessible and reachable for every kind of people. In general, a vlogcontent is all about daily activity of the content maker that tend to purpose onlyfor their existent and fun. But however, there are actually vlogs that serve usefulinformation for society in that case is travel vlog about museum in “Belajar PraSejarah di Museum Sri Baduga Bandung”. This vlog then had some analyticalprocess on its element and principle to seek if there is actually citizen journalismelement, because the purpose of a vlog is similar to citizen journalism contentfor soft news category. This research used qualitative method and constructivistparadigm with descriptive study approach to collect all the data and informationneeded through observation, in depth interview and a few documentations ofthis research. The result of this research is that vlog “Belajar Pra Sejarah diMuseum Sri Baduga Bandung” includes useful content and information forsociety about Sri Baduga Museum existent and this vlog overall is similar tocitizen journalism content in feature news category because it includes all theelement and characteristics of feature journalism and the function of press injournalism product. But however, in all conclusions this vlog needs some revisions in camera shots and contents in order to make audiens understand and find comfort in the vlog.